The Reciprocal Paradigm of Tafsīr al-Miṣbah and Tafsīr al-Taḥrīr wa al-Tanwīr on Surah al-Baqarah verse 222 about Menstruation Blood - Halya Millati (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2021)
Women's misogynistic interpretation of their menstruation period as